Spinal Instrumentation in Growing Children Retards the Natural Development of Pelvic Incidence. Issue 3 (March 2019) - Bekmez, Senol; Demirkiran, Halil Gokhan; Dede, Ozgur; Atici, Yunus; Balioglu, Mehmet Bulent; Kruyt, Moyo; Ward, Timothy; Yazici, Muharrem
Abstract : Background: Pelvic incidence increases gradually throughout growth until skeletal maturity. Growing rod instrumentation has been suggested to have a stabilizing effect on the development of the normal sagittal spinal alignment. The purpose of this study is to determine the effect of fixed sagittal plane caused by dual growing rod instrumentation on the natural progression of sagittal spinopelvic parameters in children with idiopathic or idiopathic-like early onset scoliosis. Methods: Hospital records of children with growing rod instrumentation from 4 separate institutions were reviewed retrospectively. Inclusion criteria were idiopathic or idiopathic-like early onset scoliosis, treatment with dual growing rods with lower instrumented vertebra L4 or upper and more than 2 years of follow-up. Instrumentation levels, magnitudes of major curve, thoracic kyphosis (T2-T12), lumbar lordosis (L1-S1) and pelvic incidence were recorded from preoperative and postoperative standing whole-spine radiographs. Estimated pelvic incidence was also calculated for each patient as if their spines had not been instrumented using the previous normative data. Results: A total of 37 patients satisfied the inclusion criteria. Average age at initial surgery was 7.4±1.8 years (range, 4 to 12 y). Mean follow-up time was 71±26 months (range, 27 to 120 mo). Mean preoperative Cobb angle of 59±13.5 (range, 30 to 86) degrees was reduced to 35.1±17.5 (range, 11 to 78) degrees at the last follow-up. Mean preoperative T2-T12 kyphosis angle was 46.2±14.9 degrees (range, 22 to 84 degrees). At the latest follow-up, it was 44.8±16.2 degrees (range, 11 to 84 degrees) ( P =0.93). Mean L1-S1 lordosis angle was 50.5±10.7 degrees (range, 30 to 72 degrees) preoperatively. At the latest follow-up, mean L1-S1 lordosis angle was 48.8±12.7 degrees (range, 26 to 74 degrees) ( P =0.29). Mean preoperative pelvic incidence was 45.7±7.9 degrees (range, 30 to 68 degrees). At the latest follow-up, it was 46.7±8.4 degrees (range, 34 to 72 degrees) ( P =0.303). The estimated average pelvic incidence was 49.5 degrees ( P =0.012). Conclusions: Previously reported developmental changes of the sagittal spinal parameters were not observed in children who underwent posterior spinal instrumentation. Our findings suggest that spinal instrumentation impedes the natural development of the sagittal spinal profile. Level of Evidence: Level IV—this is a retrospective case-series.